Climatic and physiological parameters related to the progress and prediction of apple sunburn damage in a neotropical climate - Vivian Severino; Mercedes Arias-Sibillotte; Santiago Dogliotti; Erna Frins; Jaime Gonzalez-Talice; José Antonio Yuri (Advances in Horticultural Science, 2020)
Apple production in neotropical climate is affected by sunburn and the high interannual variability in meteorological conditions makes prediction and management of damage difficult. Non-destructive methods associated with physiological variables are keys to monitoring but their development is still incipient. In our study occurrence of sunburn, meteorological conditions and physiological parameters was monitored throughout four crop cycles. Fruit visual assessment and reflectance measures in field, as well as, pigments, proline and hydric potential in laboratory, were accomplished. The results show that the availability of water in the soil was more related to the evolution of sunburn than air temperature. Plant Senescence Reflectance Index (non-destructive predictor) discriminated between healthy and damaged fruits and fruit hydric potential and proline content were good indicators of sunburn, although such variables are determined when damage has already occurred. Our results suggest focusing future research on the water balance of the system and on the physiological indicators of osmotic stress as a way to predict damage.